Efektivitas Kombinasi Terapi Relaksasi Benson Dan Guided Imagery Terhadap Penurunan Kecemasan Pada Ibu Hamil - Annisya, Nurul; Erika, Erika; Dewi, Yulia Irvani (Universitas Pahlawan Tuanku Tambusai, 2024)
Anxiety in pregnant women is a significant mental health issue and has the potential to affect maternal and fetal health. Relaxation therapy and guided imagery have been identified as promising interventions for reducing anxiety, but the effectiveness of the combination of these two therapies has not been widely explored. This study aims to determine the effectiveness of a combination of Benson relaxation therapy and guided imagery in reducing anxiety in pregnant women. The research method uses a quasi-experimental approach with nonequivalent control group design. The research was conducted in the working area of Payung Sekaki Public Health Center from May 16-26, 2024. The sampling technique was purposive sampling with 29 respondents from the experimental group and 29 respondents from the control group. The analysis used was bivariate analysis with an independent T test. The research results showed that the experimental group showed a significant decrease in anxiety scores from an initial average of 30.52 to 22.31, while the control group only showed a marginal decrease from 27.34 to 26.83. Statistical analysis confirmed a significant difference in the reduction of anxiety levels between the two groups (P = 0.001). Based on the results of this study, it was concluded that the combination of Benson relaxation therapy and guided imagery was effective in reducing anxiety in pregnant women.